Novel Mechanistic Insights into the Anti-cancer Mode of Arsenic Trioxide - Wahiduzzaman, Md; Ota, Akinobu; Hosokawa, Yoshitaka (Current Cancer Drug Targets, 2020)
Arsenic, a naturally-occurring toxic element, and a traditionally-used drug, has received a great deal of attention worldwide due to its curative anti-cancer properties in patients with acute promyelocytic leukemia. Among the arsenicals, arsenic trioxide has been most widely used as an anti-cancer drug. Recent advances in cancer therapeutics have led to a paradigm shift away from traditional cytotoxic drugs towards the targeting of proteins closely associated with driving the cancer phenotype. Due to the diverse anti-cancer effects of ATO on different types of malignancies, numerous studies have made efforts to uncover the mechanisms of ATO-induced tumor suppression. From in vitro cellular models to studies in clinical settings, ATO has been extensively studied. The outcomes of these studies have opened doors to establishing improved molecular-targeted therapies for cancer treatment. The efficacy of ATO has been augmented by combination with other drugs. In this review, we discuss recent arsenic-based cancer therapies and summarize the novel underlying molecular mechanisms of the anti-cancer effects of ATO.
Keywords: acute promyelocytic leukemia